PENINGKATAN KEMAMPUAN BERBICARA MELALUI MODEL TALKING STICK DIPADU DENGAN MEDIA KARTU CERITA PADA SISWA - Anwar Marasabesy; Santi M J Wahid (PEDAGOGIK, 2021)
The purpose of this research are (1) to find out the process of improving speaking skills through the Talking Stick model combined with story card media for third grade students at SDN 12 Ternate City, (2) to find out the results of improving speaking skills through the Talking Stick model combined with story card media for third grade students. SDN 12 Ternate.The process of applying the Talking Stick model combined with story card media is divided into several steps of learning activities as follows: (1) Divide students into 5 groups, (2) Distribute story cards to each student, (3) Provide an explanation of the Talking Stick learning model combined with story card media, (4) Students discuss with their group friends, then each write about events such as on the story cards that have been distributed, (5) After that students make a circle, (6) The teacher gives a stick to a student, while singing the song the student rolls the stick to his friend, (7) the student who gets the stick, must speak in front of the class according to the material received.Improved speaking skills through the application of the Talking Stick model combined with story card media which shows the mastery of students by 25% or 6 students who complete the 24 students who take part in the learning process in class with the average score in the first cycle is 56.50%. While in the second cycle the percentage of students increased to 87.50% or 21 students who completed the 24 students who took part in the learning process in class with the average score in the second cycle was 73.25%. Therefore, the application of the Talking Stick model combined with story card media can improve the speaking ability of third grade students at SDN 12 Ternate as seen from the results of cycle I and cycle II.